The Use of Digital Media to Improve Reading Skills in Indonesian Language Learning in Elementary Schools: A Literature Review - Maryati Rina Sari; Yasinta Mahendra (Journal for Lesson and Learning Studies, 2025)
Indonesian language learning in elementary schools still faces various challenges, particularly low student interest in reading. This problem is exacerbated by teaching methods that tend to be monotonous and lack innovation, thereby hindering the comprehensive development of language skills. In fact, reading skills are a key foundation in the educational process, but many students are unable to achieve optimal development due to these limitations. In this context, digital media offers a promising solution by providing interactive and engaging features that can boost students' motivation and reading abilities.The purpose of this study is to identify and analyze the effectiveness of the use of digital media in improving reading skills in Indonesian learning in elementary schools through a comprehensive literature review approach. This study uses the Literature review method with the PRISMA approach. The results of the study show a consistent trend of increasing article publication from 2020 to 2024, which indicates a growing interest in research on the use of digital media in improving reading skills in elementary schools. Therefore, it can be concluded that the use of digital media has proven to be effective in improving the reading skills of elementary school students in learning Indonesian, with various types of media and methods that have a positive impact.  However, further research is needed to explore the contextual and long-term aspects that affect the effectiveness of digital media, as well as develop practical guidelines for teachers and media developers to optimize their use in learning.